The Internet in Asia through Singapore. Issue 4 (1st December 2018) - Graham, Connor; Kerr, Eric; Pang, Natalie; Fischer, Michael M. J.
Abstract: The Internet or, as these authors argue, Internets (plural) in Asia are composed of cables and exchanges, protocols and firewalls, regulations and other legal devices, making them subject to investment and governance strategies, as well as treaties and court cases. But they are also composed of figures, layers, stories, and rumors. These latter descriptors provide a heuristic framework of social features that, together with metaphors from folklore, provide analytic tools for understanding the diversity, conflicts, competitions, and disengagements of the patchwork of Internet development across Asia. The authors further argue that Singapore provides an exceptionally valuable comparative site from which to explore these features. The first part of this article lays out some of the comparative features, and the second part turns to the four themes or heuristics of figures, layers, stories, and rumors, developed through an STS research cluster at the Asia Research Institute and Tembusu College, both at the National University of Singapore.